An Economic History of Twentieth-Century Latin America
XIV, 345 p. 3 illus.
Keywords: In the 1990s, 'protection', 'import substitution' and 'intervention' have become dirty words, part of the 'leyenda negra' of Latin America development in the postwar period. This book attempts a fresh look at the controversial years between the end of the Second World War and the point when, at varying dates in different countries, a discontinuity occurs in which the postwar 'style of development' ceased to play a central role in the economic evolution of the region. The analysis is based on seven case studies covering eleven countries.